Diameter assessment of soilcrete column using in-hole electrical resistivity tomography. Issue 12 (11th December 2020) - Lin, Chun-Hung; Lin, Chih-Ping; Ngui, Yin Jeh; Wang, Haoran; Wu, Po-Lin; He, Guan-Jie; Liu, Hsin-Chang
Abstract : Quality control of jet grouting at large depth is a challenging task. An in-hole electrical resistivity method was recently shown to have high potential for assessing the diameter and integrity of jet grouting. To facilitate visualised inspection and practical use of the in-hole resistivity method for jet grouting, this study introduces a novel and practical tomographic approach. An analogous mapping approach from axially symmetric in-hole electrical resistivity tomography (ERT) to two-dimensional (2D) half-space surface ERT is proposed, allowing direct implementation of widely available 2D inversion software. A quantitative reduction method is also proposed to determine accurately the variation of column diameter from the inverted tomogram. Numerical simulations validate the proposed approach and show that the estimation error is within 10% when the electrode spacing is less than 1/5 of the column diameter. The spatial resolution and the effect of axially asymmetric condition are numerically investigated, the latter suggesting the importance of centralising electrodes in the soilcrete column. Two physical model tests are performed and verify the performance of the proposed method experimentally.